Diagnostic issues in difficult-to-treat rheumatoid arthritis: a systematic literature review informing the EULAR recommendations for the management of difficult-to-treat rheumatoid arthritis. Issue 1 (29th January 2021) - Roodenrijs, Nadia M T; Kedves, Melinda; Hamar, Attila; Nagy, György; van Laar, Jacob M; van der Heijde, Désirée; Welsing, Paco M J
Abstract : Objectives: To summarise the evidence on diagnostic issues in difficult-to-treat rheumatoid arthritis (D2T RA) informing the EULAR recommendations for the management of D2T RA. Methods: A systematic literature review (SLR) was performed regarding the optimal confirmation of a diagnosis of rheumatoid arthritis (RA) and of mimicking diseases and the assessment of inflammatory disease activity. PubMed and Embase databases were searched up to December 2019. Relevant papers were selected and appraised. Results: Eighty-two papers were selected for detailed assessment. The identified evidence had several limitations: (1) no studies were found including D2T RA patients specifically, and only the minority of studies included RA patients in whom there was explicit doubt about the diagnosis of RA or presence of inflammatory activity; (2) mostly only correlations were reported, not directly useful to evaluate the accuracy of detecting inflammatory activity in clinical practice; (3) heterogeneous, and often suboptimal, reference standards were used and (4) (thus) only very few studies had a low risk of bias. To ascertain a diagnosis of RA or relevant mimicking disease, no diagnostic test with sufficient validity and accuracy was identified. To ascertain inflammatory activity in patients with RA in general and in those with obesity and fibromyalgia, ultrasonography (US) was studied most extensively and was found to be the most promising diagnostic test. Conclusions: This SLR highlights the scarcity of high-quality studies regarding diagnostic issues in D2T RA. No diagnostic tests with sufficient validity and accuracy were found to confirm nor exclude the diagnosis of RA nor its mimicking diseases in D2T RA patients. Despite the lack of high-quality direct evidence, US may have an additional value to assess the presence of inflammatory activity in D2T RA patients, including those with concomitant obesity or fibromyalgia.